Tools for Addressing Microaggressions: An Interactive Workshop for Perioperative Trainees - LaMisha Hill Weller; Janette Tang; Rebecca Chen; Christy Boscardin; Odinakachukwu Ehie (Association of American Medical Colleges, 2023)
Introduction Graduate trainees from diverse backgrounds may experience discrimination, mistreatment, and microaggressions. While the ability to identify and respond to microaggressions is a much-needed skill for all emerging trainees, limited training workshops exist for residents, especially within perioperative medicine. To embody the principles of diversity, equity, inclusion, and anti-racism (DEIA), we aimed to empower trainees in the perioperative environment with several strategies for addressing microaggressions to bridge this training gap. Methods Based on critical race theory, transformative learning, minority stress theory, and the structural theory of gender and power, this workshop was developed with the primary aim of educating trainees on microaggressions, amplifying the role of allyship, and providing tools to respond to microaggressions as an ally. We used a mixed methods approach to examine participants' pre/post self-evaluations of microaggression intervention tools and the overall effectiveness of the workshop. Results The postsurvey captured the experiences of 54 trainees, including 37 of 44 (84%) first-year clinical anesthesia residents and 14 of 24 (58%) surgery residents. The facilitator and course feedback was remarkably positive. Paired t test analyses on participants' pre- and postsurvey responses demonstrated a statistically significant increase in knowledge of microaggressions. This workshop also significantly increased learners' self-reported tools for responding to microaggressions. Discussion Overall, these promising findings suggest that the strategies presented in this workshop could be applied across other graduate medical education programs. Institutions may wish to customize workshop elements, such as the case scenarios, and the workshop can also be incorporated within a DEIA curriculum.